Pengaruh Pemasaran Digital dan Kesadaran Merek terhadap Keputusan Pembelian di Store Zoya - Wala Erpurini; Maman Rukmana; Syifa Aulia Fajrin (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine the effect of digital marketing and brand awareness on purchasing decisions at Zoya Bandung Indah Plaza. The population of this study includes members who buy products at Zoya Bandung Indah Plaza. The survey subjects in this study amounted to 100 people. This research method uses descriptive and linked research methods. This method considers the influence between the independent variable and the dependent variable. The results of the descriptive analysis research show that digital marketing and brand awareness on purchasing decisions at Zoya Bandung Indah Plaza are very good. The data analysis technique used is link test path analysis. It shows that the influence of digital marketing on purchasing decisions is 2%, the influence of brand awareness on purchasing decisions is 387 % of the influence of brand awareness and digital marketing on purchasing decisions at Zoya Bandung Indah Plaza is 829%.